Soviet Diplomacy: Waging and Winning Its Own War – Introduction to the Forum - K. M. Barsky (Vestnik MGIMO-Universiteta, 2024)
This editorial introduces a series of papers based on presentations made at the "Soviet Diplomacy during World War II" conference held at MGIMO on June 30, 2023. It draws attention to notable aspects of Soviet diplomacy during the wartime period. Firstly, it highlights the persistent effort and skill in negotiating despite significant divergences in interests and approaches. Secondly, it discusses the adeptness in striking a careful balance between steadfastly maintaining one's stance and employing flexibility and pragmatism to achieve the ultimate objective of victory over the enemy. Thirdly, the article examines the history of international negotiations during World War II as an illustration of the clash and collaboration among prominent political figures, notably emphasizing how I.V. Stalin often outplayed his counterparts in this personalized “diplomacy of leaders.”The history of World War II compellingly illustrates the necessity of diplomacy, not only during the conflict but also in the transition to peace and negotiations thereafter, as well as in the establishment of a new global order.